2021
DOI: 10.1002/prca.202100042
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiles of Zika virus‐infected placentas bearing fetuses with microcephaly

Abstract: Purpose Zika virus (ZIKV) transmission to the fetus during pregnancy could enable a collection of severe fetal malformations like microcephaly (MC), termed Congenital Zika Syndrome (CZS). The mechanisms involved in ZIKV transplacental transmission are not fully understood. Experimental Design Here we aim to identify in placental tissues the deregulated proteins associated with ZIKV‐induced MC using label‐free proteomics. Results We found proteins associated with DNA damage and gene expression inhibition up‐reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…Numerous proteomic and transcriptomic studies have been conducted to explain ZIKV infection in microcephalic fetuses, primary human fetal neural progenitor cells, serum samples, placental tissues, and astrocyte-derived cell lines [ 45 , 46 , 47 , 49 ]. This study identified numerous cellular proteins, some of which were similar to previous studies while others were novel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous proteomic and transcriptomic studies have been conducted to explain ZIKV infection in microcephalic fetuses, primary human fetal neural progenitor cells, serum samples, placental tissues, and astrocyte-derived cell lines [ 45 , 46 , 47 , 49 ]. This study identified numerous cellular proteins, some of which were similar to previous studies while others were novel.…”
Section: Discussionmentioning
confidence: 99%
“…Among the similarities, fibronectin was found to be downregulated by ZIKV in U251 cells in this study. Our previous SOMAScan proteomic study also implicated ZIKV-induced damage to placental integrity [ 45 , 54 ]. Cytokines and chemokines such as IL-6 were identified as downregulated while IL-8 and CCL5 were upregulated in this study ( Table 2 ) and in our previous study [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteome Discoverer software version 2.1 (Thermo Fisher Scientific, Waltham, MA, USA) was employed for the raw data processing. Protein identification was carried out according to Quiñones-Vega et al [ 22 ]. Three protein databases were used (all downloaded in September 2022): (i) Arabidopsis thaliana UniProt database ( ), accessed on 29 September 2022), (ii) plant viruses + taxonomy_id:33090 + PMeV from Uniprot database ( ), accessed on 29 September 2022), and (iii) Carica papaya NCBI database ( Carica papaya ) AND “ Carica papaya ”[porgn:__txid3649].…”
Section: Methodsmentioning
confidence: 99%
“…Here, we achieve a comprehensive analysis between the AF metabolomics data and our previous AF, placenta, and brain proteomics data [14,15,47] from a broad perspective of the molecular pathways in common. In our ZIKV-infected placenta proteomics study [47], fatty acid synthase was increased four times in concentration in the microcephalic fetuses, which suggests an enhanced fatty acid synthesis to use in viral replication [23]. Interestingly, ATP synthase and ADP/ATP translocase presented a decreased concentration in microcephalic fetuses, which could be related to mitochondrial dysfunction caused by fatty acid accumulation [48].…”
Section: Multi-omics Analysismentioning
confidence: 99%